Regulation of public property syndication schemes under the Companies Act 71 of 2008 and the Consumer Protection Act 68 of 2008 - Delport, Petrus Albertus (University of Pretoria, 2015)
Mini Dissertation (LLM)--University of Pretoria, 2015.